2019
DOI: 10.1371/journal.pone.0216645
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome of Camellia japonica genome structures, comparative and phylogenetic analysis

Abstract: Camellia is an economically, ecologically and phylogenetically valuable genus in the family Theaceae. The frequent interspecific hybridization and polyploidization makes this genus phylogenetically and taxonomically under controversial and require detailed investigation. Chloroplast (cp) genome sequences have been used for cpDNA marker development and genetic diversity evaluation. Our research newly sequenced the chloroplast genome of Camellia japonica using Illumina HiSeq X T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 56 publications
11
63
0
Order By: Relevance
“…The most abundant were mononucleotide repeats, located in non-coding regions, and contributed to AT richness ( Figure 3). These results are consistent with most reported angiosperms [23][24][25][26][28][29][30]. The total number of SSRs was 237 in A. katsumadai, 244 in A. oxyphylla sampled from Guangdong, 247 in A. pumila, 236 in A. zerumbet, and 241 in A. oxyphylla sampled from Hainan ( Figure 3A).…”
Section: Ssrs and Long Repeats Analysessupporting
confidence: 90%
See 2 more Smart Citations
“…The most abundant were mononucleotide repeats, located in non-coding regions, and contributed to AT richness ( Figure 3). These results are consistent with most reported angiosperms [23][24][25][26][28][29][30]. The total number of SSRs was 237 in A. katsumadai, 244 in A. oxyphylla sampled from Guangdong, 247 in A. pumila, 236 in A. zerumbet, and 241 in A. oxyphylla sampled from Hainan ( Figure 3A).…”
Section: Ssrs and Long Repeats Analysessupporting
confidence: 90%
“…The contractions and expansions at the borders of IR regions were common evolutionary events and may cause size variations of chloroplast genomes [13,[23][24][25][26][27][28][29][30]. We compared the IR-SC boundaries information of the five Alpinia chloroplast genomes ( Figure 5).…”
Section: Ir Contraction and Expansion Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other angiosperms (Nie et al 2012;Liu et al 2013;Chi et al 2018;Yan et al 2019), the coding regions of seven Saxifragaceae chloroplast genomes are more conservative than the non-coding regions. Among the ten most divergent coding regions in this study, matK has been considered as core universal DNA barcodes in many species (Li et al 2019), and ycf1 has recently been widely applied in plant phylogeny and DNA barcoding studies (Dong et al 2015;Yang et al 2017). Besides, accD, rps19, ccsA and ndhF have also been proved to exhibit large divergence among various plant lineages and can be applied in phylogenetic studies (Ni et al 2016;Ivanova et al 2017).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, comparing the complete chloroplast genome of S. sinomontana with that of other six Saxifragaceae species, we found that the size of S. sinomontana chloroplast genome is the smallest among the compared Saxifragaceae species, but the organization and gene content is highly similar. Chloroplast SSRs usually exhibit high levels of variations and are widely used in polymorphism investigations, population genetics and phylogenetic analyses (Powell et al 1995;Provan et al 1999Provan et al , 2001Flannery et al 2006;Xue et al 2012;Li et al 2019). For S. sinomontana, the number of cpSSRs (sixty-one) is moderate compared with other species of angiosperms (Liu et al 2013;Fu et al 2016;Yan et al 2019).…”
Section: Discussionmentioning
confidence: 99%